2012
DOI: 10.1259/dmfr/22131776
|View full text |Cite
|
Sign up to set email alerts
|

Variation in costs of cone beam CT examinations among healthcare systems

Abstract: Objectives: To analyse the costs of cone beam CT (CBCT) in different healthcare systems for patients with different clinical conditions. Methods: Costs were calculated for CBCT performed in Cluj (Romania), Leuven (Belgium), Malmö (Sweden) and Vilnius (Lithuania) on patients with (i) a maxillary canine with eruption disturbance, (ii) an area with tooth loss prior to implant treatment or (iii) a lower wisdom tooth planned for removal. The costs were calculated using an approach based on the identification, measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 11 publications
0
23
0
Order By: Relevance
“…The estimated costs of a CBCT examination varied considerably across the four healthcare systems studied. 70 Only one RCT seems to exist, which has included a calculation of absolute and relative costs prospectively for a CBCT compared with a PAN examination. 68 In this RCT, it was found that costs for a CBCT examination were three to four times the costs for PAN examination when used for treatment planning before mandibular third molar removal.…”
Section: Level 3-effect On Diagnostic Thinkingmentioning
confidence: 99%
See 1 more Smart Citation
“…The estimated costs of a CBCT examination varied considerably across the four healthcare systems studied. 70 Only one RCT seems to exist, which has included a calculation of absolute and relative costs prospectively for a CBCT compared with a PAN examination. 68 In this RCT, it was found that costs for a CBCT examination were three to four times the costs for PAN examination when used for treatment planning before mandibular third molar removal.…”
Section: Level 3-effect On Diagnostic Thinkingmentioning
confidence: 99%
“…Cost analysis provides an important input for economic evaluations in comparing costs and consequences of diagnostic methods in different healthcare systems and for planning service delivery in both public and private sectors. 70 Furthermore, when radiographic methods are under evaluation, estimates for radiation-derived cancers should be included in assessment of societal costs. One epidemiologic study estimated costs for a CBCT examination, if undertaken, in all dental clinics in the country before third molar removal.…”
Section: Level 3-effect On Diagnostic Thinkingmentioning
confidence: 99%
“…The success of CBCT is mainly due to a relatively low radiation dose [11], limited metal artefacts [12], high spatial resolution (0.075-0.4 mm isotropic voxel) [13], and low maintenance and operating costs [14]. Nevertheless, CBCT is not used for contrast-enhanced examinations, does not have a high contrast resolution [15], and the scan time is long with non-negligible motion artefacts [16].…”
Section: Introductionmentioning
confidence: 99%
“…3 Very few studies in dentistry have evaluated societal and economic aspects of a new technology, 4 and in dental radiology only four studies concerning this subject were identified in a recent review. [4][5][6][7] One of the most common surgical procedures in dentistry is removal of mandibular third molars. 8 The anatomy of the area facilitates the risk for temporary or permanent neurosensory disturbances.…”
Section: Introductionmentioning
confidence: 99%
“…However, only one study seems to have assessed the resources used when implementing CBCT in dental procedures describing differences between some countries with respect to cost structures. 7 The aim of this prospective clinical study was to derive the absolute and relative costs of CBCT and panoramic imaging before surgical removal of an impacted mandibular third molar. Furthermore, the study aimed to analyse the influence of different cost setting scenarios on the outcome of the absolute and relative costs and the incremental costs related to surgery.…”
Section: Introductionmentioning
confidence: 99%